+0  
 
0
59
1
avatar

Am I correct? please help ASAP!!!!

 Feb 14, 2020
 #1
avatar+109740 
+1

y = -x^2 -5x -6      (1)

 

x + y = -3     →    y = -3 -x     (2)

 

Sub (2)  into (1)  for   y    and we have

 

-3 - x = -x^2  - 5x   - 6        add  3 , x to  both sides

 

-x^2 - 4x  - 3   = 0             multiply through  by  -1

 

x^2 + 4x + 3  =  0    factor

 

(x + 3)  ( x + 1)  = 0

 

Set both fctors to 0  and solve for x and we get that

 

x = -3   and     x = -1

 

And when x = -3   y  =  0

 

And when  x =  -1     y = -2

 

So you are CORRECT  !!!    [ good job  !!! ]

 

 

cool cool cool

 Feb 14, 2020

54 Online Users

avatar
avatar
avatar
avatar
avatar
avatar